Training on making an online store with the TokoTalk application in Sidomulyo Village, Kutai Kartanegara - Prapdopo Prapdopo; Armini Ningsih; Indriyani Dewi Lestari; Anggi Agustina Dinda Permatasari (Community Empowerment, 2021)
During the Covid-19 pandemic, mothers in Sidomulyo Village have been selling online through social media. The potential of the creative economy that already exists in Sidomulyo Village needs to be further developed both in terms of product quality, packaging and even marketing. This service aims to provide promotional media to raise the image of micro business products in Kutai Kartanegara Regency, especially in Sidomulyo Village using the TokoTalk application. This application provides a very complete range of features and services to develop an online business that is easy, practical, and free. After the training, the people of Sidomulyo Village have been able to create and manage their online store well, so it is hoped that they can improve their welfare.